Atomic clusters in decagonal Al–Cr–Fe : hexagon, star and decagon - Li, Rui Tao (2020)
In this study, the atomic arrangement of the decagonal phase in a spark-plasma-sintered Al–Cr–Fe alloy has been studied by Cs-corrected high angle annular dark field scanning transmission electron microscopy (HAADF STEM) for the first time. We have found that three types of atomic clusters exist as basic structural units: star, flattened hexagon and decagon with an edge-length of 0.65 nm. These three types of units are linked to each other by sharing edges or inter-penetrating, with adjacent star clusters overlapping each other. The respective structural models of these structural units are proposed from the HAADF STEM images.